Exploring the Implementation of Task-Based Language Learning Model: a Review of Studies on Students' Perceptions - ilham ilham (Linguistics and ELT Journal, 2021)
This study attempt to investigate the students’ perception on the implementation of Task-Based Language Learning (TBLL) Model. The study involved 18 EFL students as the participants. The data was collected from questionnaire that were administered to all participants and interviews to some students as the representatives.  The result showed that the developed model which highlights teaching steps, classroom situation, time allocation, writing activities, and lecturers' performance in the class and the teaching materials are effective to facilitate students to learn and improve their writing skills. The result of this study also revealed that the developed model was perceived by the students to be very well structured because the learning stage started from introducing to presenting stage, the interaction between the lecturers and the students in the academic writing course was very responsive, the students thought that the lecturers treated the students well, most students had positive perceptions of the teaching materials of academic writing subjects and they felt the learning objectives were achieved. They were able to write topic sentences and composed a full text, their writing structure was better, and they recognized the small things. Then, students became more active, motivated and their understanding of the topic was increased.